Still Living, Loving, and Laughing: Spiritual Life in the Dementia Unit - Perkins, Christine (Journal of religion, spirituality & aging, 2015)
Semi-structured interviews, conducted with dementia unit residents, family, and staff members provided a three-way perspective on the spirituality of residents. The issues covered included: what gives meaning to life, how difficulties are coped with and hope maintained. Themes identified were: the importance of relationships, the retention of identity, and the progression of dementia. These themes are interdependent with relationships being important both in giving meaning in themselves and in assisting with the maintenance of identity, especially as cognitive function deteriorated. An identifiable and relating person remains despite dementia. Provided appropriate assistance, the person with advanced dementia is able to value and engage in spiritual practices that provide ongoing meaning at times of great uncertainty and difficulty.